sửa đề : \(\left(2n-1\right)^3-\left(2n-1\right)\)
đề đó mình nghĩ vậy
\(\left(2n-1\right)^3-\left(2n-1\right)\)
\(=\left(2n-1\right)\left(\left(2n-1\right)^2-1\right)\)
\(=\left(2n-1\right)\left(\left(2n-1\right)^2-1^2\right)=\left(2n-1\right)\)
\(=\left(2n-1-1\right)\left(2n-1+1\right)\)
\(=\left(2n-1\right).\left(2n-2\right).2n\)
\(=\left(2n-1\right).2\left(n-1\right).2n\)
\(=\left(2n-1\right)4.n\left(n-1\right)\)
n(n-1) chia hết cho 2 và là tích hai số liên tiếp nên
\(\left(2n-1\right).4.n\left(n-1\right)⋮\left(2.4\right)=8\)( đpcm )